2022
DOI: 10.1371/journal.pone.0269386
|View full text |Cite
|
Sign up to set email alerts
|

Identification of critical genes and molecular pathways in COVID-19 myocarditis and constructing gene regulatory networks by bioinformatic analysis

Abstract: Background There is growing evidence of a strong relationship between COVID-19 and myocarditis. However, there are few bioinformatics-based analyses of critical genes and the mechanisms related to COVID-19 Myocarditis. This study aimed to identify critical genes related to COVID-19 Myocarditis by bioinformatic methods, explore the biological mechanisms and gene regulatory networks, and probe related drugs. Methods The gene expression data of GSE150392 and GSE167028 were obtained from the Gene Expression Omni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Exploring the genetic implications, several studies conducted between 2008 and 2022 outlined the influence of MTX on genes such as TYMS, CTP, BCL-3, CDC20, CENPF, FAIM3, POLD3, RPA3, and RNASEH2A. The mechanisms ranged from inhibiting crucial enzymes in the folate pathway, affecting nucleotide metabolism, and causing chromosomal instability, to interfering with DNA repair and synthesis processes (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…Exploring the genetic implications, several studies conducted between 2008 and 2022 outlined the influence of MTX on genes such as TYMS, CTP, BCL-3, CDC20, CENPF, FAIM3, POLD3, RPA3, and RNASEH2A. The mechanisms ranged from inhibiting crucial enzymes in the folate pathway, affecting nucleotide metabolism, and causing chromosomal instability, to interfering with DNA repair and synthesis processes (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…KIF20A is highly expressed in almost all cancers, including gastric cancer [54], melanoma [55], hepatocellular carcinoma [56], and breast cancer [57]. Several studies have also shown that KIF20A is a hub gene involved in SARS-coV-2 infection [58,59]. TPX2 is a microtubule-associated protein that activates the cell cycle kinase protein Aurora-A, which then plays an vital role in spindle formation in mitosis [60], and high TPX2 expression is associated with tumor progression and low survival in gastric cancer [61].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2-facilitated host cell death is inseparable from nucleocapsid (N) protein-dependent G1 cell cycle arrest mechanism, and this N protein is also involved in viral replication and transcription, and many stages of the viral life cycle ( 30 ). Interestingly, much research on SARS-CoV-2 infection and other comorbidities, such as myocarditis ( 31 ), cardiac injury ( 32 ), and Alzheimer’s disease ( 33 ), also found that genetic alteration of cell cycle-related genes was very significant in the pathogenesis. Ubiquitination signaling is crucial for immunity to limit the spread of pathogens, thus, it plays a critical role in the viral pathogenicity of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%